COMPARATIVE CHARACTERIZATION OF SEVOFLURANEAND DESFLURANE-BASED ANESTHETIC MAINTENANCE AND POSTANESTHETIC AWAKENING PERIODS IN OUTPATIENT SURGERY - M. R. Khalimov; A. M. Ovezov; O. A. Grebenchikov; M. A. Shapkin; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии)
Objective: to study the specific features of sevoflurane and desflurane-based anesthetic maintenance and awakening periods in outpatient surgery. Subjects and methods. The course of intraoperative and immediate postoperative periods was analyzed in 125 patients. By using the envelope method, the patients were randomized to one of two study groups according to the mode of anesthesia: 1) desflurane-based anesthesia (n = 62); 2) sevoflurane-based anesthesia (n = 63). Results. During surgery, all group 1 patients needed mechanical ventilation to maintain adequate gas exchange. This is probably associated with the use of the fairly high dose of fentanyl, which is required to ensure adequate analgesia. With equal fresh gas streams, the consumption of desflurane doubled that of sevoflurane. The postanesthetic awakening period turned out to be equal in both groups. The length of awakening unit stay after anesthesia with desflurane proved to be shorter than after that with sevoflurane. Conclusion. Desflurane-based anesthesia is attractive when it is important to reduce the length of postoperative unit stay as far as possible. If 10–12 more minutes are uncritical to do this, sevoflurance-based anesthesia is preferable.